2017
DOI: 10.1097/yco.0000000000000327
|View full text |Cite
|
Sign up to set email alerts
|

Application of olfactory tissue and its neural progenitors to schizophrenia and psychiatric research

Abstract: Purpose of review The goal of this review article is to introduce olfactory epithelium (OE)-derived cell/tissue models as a promising surrogate system to study the molecular mechanisms implicated in schizophrenia (SZ) and other neuropsychiatric disorders. Here we particularly focus the utility of their neural progenitors. Recent findings Recent investigations of the pathophysiology of SZ using OE-derived tissue/cell models have provided insights about SZ-associated alterations in neurodevelopment, stress res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 61 publications
1
27
0
Order By: Relevance
“…Thanks to their low invasiveness and high scalability, ON cell models have been put forward as promising surrogates to explore neuronal biomarkers in SCZ, providing a unique opportunity to unveil novel potential molecular targets for diagnosis and treatment [19]. To our knowledge, this is the first study applying SR-FTIR spectroscopy in ON cells to study the macromolecular alterations in SCZ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thanks to their low invasiveness and high scalability, ON cell models have been put forward as promising surrogates to explore neuronal biomarkers in SCZ, providing a unique opportunity to unveil novel potential molecular targets for diagnosis and treatment [19]. To our knowledge, this is the first study applying SR-FTIR spectroscopy in ON cells to study the macromolecular alterations in SCZ.…”
Section: Discussionmentioning
confidence: 99%
“…Obtaining viable neurological tissue to study how biomarkers of disease are modulated by drugs such as cannabis in living patients has proven challenging. In this sense, the olfactory neuroepithelium (ON) has great potential as a surrogate model of central nervous system function to study the molecular processes involved in some neuropsychiatric disorders such as SCZ [19]. Human olfactory sensory neurons are replaced and generated by neurogenesis continuously, throughout all the adult life, from neuronal precursors located in the apical and basal membranes [20].…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies support the notion that olfactory mucosa may reflect pathology of the central nervous system, e.g., in Parkinson's disease, schizophrenia, and rodent tauopathy models [26,31,39,42]. Interestingly, Moon et al found higher levels of miRNA-206 in olfactory mucosa in MCI and even more in manifest AD as compared to controls, thus supporting the suitability of olfactory mucosa tissue as a possible biomarker [30].…”
Section: Discussionmentioning
confidence: 69%
“…Addressing this question in the context of schizophrenia warrants the use of longitudinal studies in which epigenetic signatures can be followed-up in the same subjects from premorbid and high-risk states to the eventual onset of fullblown psychosis. Such longitudinal investigations, however, will require the use of easily accessible tissues such as peripheral blood, saliva, and olfactory epithelium (149). Even if epigenetic signatures in peripheral tissues might not necessarily capture disease-associated epigenetic changes occurring in the CNS (Tables 1 and 2), they can provide valuable information regarding the clinical course of schizophrenia, including conversion from a high-risk state to first-onset psychosis (50).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%